Electronic Cigarettes and Vaping-Associated Lung Injury (EVALI): A Rural Appalachian Experience. Issue 2 (15th March 2021) - Sangani, Rahul; Rojas, Edward; Forte, Michael; Zulfikar, Rafia; Prince, Nicole; Tasoglou, Antonios; Goldsmith, Travis; Casuccio, Gary; Boyd, Jonathan; Olfert, I. Mark; Flanagan, Melina; Sharma, Sunil
ABSTRACT: Background: Electronic cigarette use has increased dramatically since their introduction in 2007. Respiratory complications, particularly lipoid pneumonia, have been reported as early as 2012. An outbreak of pulmonary injury in 2019 has been reported in patients using vaping products. Research Question: To describe a rural Appalachian tertiary center's experience of EVALI and to identify novel mechanisms of pulmonary injury patterns. Study Design and Methods: We present a consecutive case series of 17 patients admitted to our rural, academic, tertiary care institution with EVALI from August 2019 to March 2020. Demographics, baseline characteristics, co-morbidities, vaping behavior, and hospital course were recorded. Broncho-alveolar lavage specimens were assessed for lipid-laden macrophages and hemosiderin-laden macrophages with stains for Oil-Red-O (n = 15) and Prussian Blue (n = 14) respectively. The patient volunteered e-liquid materials (n = 6), and vapors were analyzed using a proton transfer reaction time-of-flight mass spectrometer (PTR-TOF-MS) to describe the chemical profile. Post-discharge interviews were conducted. Results: The most common CT finding was bilateral ground-glass opacities with a predilection for lower lung zones. The most frequent pulmonary injury pattern was lipoid pneumonia. The majority of EVALI patients were critically ill requiring ventilation or ECMO. The most severely ill patients were noted to be positive for iron stains in macrophages and showed higher volatile organic compound (VOC) levels in chemical analysis. Interpretation : Based on our experience, EVALI in rural Appalachia presented with relatively severe respiratory failure. Worse outcomes appear to be correlated to high levels of VOCs, iron deposition in lungs, and concomitant infection.